Corporeity and affectivity : dedicated to Maurice Merleau-Ponty - Novotný, Karel, 1964-; Rodrigo, Pierre.; Slatman, J.; Stoller, Silvia. (Studies in Contemporary Phenomenology, 2013)
The articles in this volume reflect upon the intersections of corporeity and affectivity in Maurice Merleau-Ponty's phenomenology. They illuminate the meaning of his phenomenology regarding corporeity and affectivity from various phenomenological perspectives. Corporeity and Affectivity explores his invaluable contribution in interdisciplinary and trans-disciplinary respect, including the humanities, the arts and the sciences. Contributors include: Alexei Chernyakov (†), Jagna Brudzińska, Universität Köln, IFiS PAN Warschau , Nicola Zippel, Sapienza University of Rome, Department of Philosophy , Karel Novotný, Faculty of Humanities, Charles University of Prague , James Mensch, Charles University in Prague, Faculty of Humanities , Annabelle Dufourcq, Charles University Prague, Faculty of Humanities , Juho Hotanen, University of Helsinki , Silvia Stoller, Universität Wien , Pierre Rodrigo, Université de Bourgogne, Dijon , Antonino Firenze, University Pompeu Fabra, Barcelona , Shaun Gallagher, University of Memphis, Department of Philosophy , Kwok-ying Lau, The Chinese University of Hong Kong , Monika Murawska, The Academy of Fine Arts, Warsaw , Irene Breuer, Bergische Universität Wuppertal , Mauro Carbone, Université "Jean Moulin" Lyon 3, Faculté de philosophie , László Tengelyi, Bergische Universität Wuppertal , Björn Thorsteinsson, University of Oceland, Institute of Philosophy , Mikkel B. Tin, Telemark University College, Porsgrunn , Tamás Ullmann, ELTE University of Budapest, Institute of Philosophy , Johann P. Arnason, La Trobe University, Melbourne; Charles University, Faculty of Humanities, Prague , Michael Staudigl, Vienna University, Department of Philosophy , Suzi Adams, Flinders University, Adelaide